Canada and the United States: An Historical and Neo-Institutional Study of Public Housing and Health Policies - Jones, Ruth J.E. (My University, 2000)
This thesis seeks to explain the way in which assisted housing and health policies evolved in Canada and the United States during four watershed periods: the mid-1940s, the late 1960s, the late 1970s, and the mid-1980s. To achieve this objective, it discusses the concepts of health, the broader determinants of health, disease prevention, and health promotion; it reviews documents which urge that greater attention be paid to the broader determinants of health during policy formulation; and it examines recent studies which stress the value of linking assisted housing and health policies.
After an overview of assisted housing and health policy development in Europe, the thesis explores the evolution of these policy fields in Canada and the United States up to the mid-1940s, and investigates the reasons why these nations followed the policy paths they did.
Using the neo-institutional approach to explain the complex interplay among the various institutions, actors, and events that affect the public policy process, the thesis discusses eight major institutional and behavioral variables that contribute to the shaping of policy over time. It then studies the influence which these variables had on assisted housing and health policies during the four watershed periods.
Examination of postwar Canadian and US policy trends shows that although housing was treated in both countries mainly as an economic issue and only secondarily as a determinant of well-being, Canada dealt with healthcare essentially as a social issue and adopted a public system, while the US treated it as a socioeconomic issue and relied heavily on the private sector. Despite these policy differences, a potential for linking assisted housing and health policy manifested itself in both countries during the mid-1940s and late 1960s, but declined after the late 1970s.
Keywords: PhD; Political Science; Canada; U.S.; Health; American Politics; International Relations; Models and Methods; Other Political Science; Political Science; Political Theory; American Politics